Attribution of Detected Temperature Trends in Southeast Brazil - R. C. deAbreu; S. F. B. Tett; A. Schurer; H. R. Rocha (Geophysical Research Letters)
Abstract Southeast Brazil has great economic importance for Brazil and is highly vulnerable to extreme events like floods and droughts. Studies have shown an increase of temperature in this region. Using a new detection and attribution framework (Ribes et al., 2017, https://doi.org/10.1007/s00382-016-3079-6) and Coupled Model Intercomparison Project Phase 5 models, this change is found to be largely due to greenhouse gases. We estimate that greenhouse gases contribute a warming of 0.95 to 1.5 °C to the observed warming trend of 1.1 °C between 1955 and 2004. Temperature changes from natural and nongreenhouse gas anthropogenic forcing are estimated to be small over this period. Results are robust using different time windows. Using the Community Earth System Model ensembles to evaluate the impacts of internal variability, observational and model error shows that most uncertainty arises from model error.